Abundances of coccolithophores found in southern Patagonia during the austral early-spring 2017 - Francisco Díaz-Rosas; Catharina Alves-de-Souza; Emilio Alarcon; Eduardo Menschel; Humberto E González; Rodrigo Torres; Peter von Dassow (PANGAEA, 2021)
Physical and chemical parameters and associated coccolithophores species/Emiliania huxleyi morphotypes abundances and biovolume and co-occurring microplankton abundances recorded in southern Patagonia (~ 50-54 S) during the austral late-spring 2015 (at the end of november) and early-spring 2017 (at the end of september). Given the scarcity of data about coccolithophores in Patagonian waters and the impressive nearly a century spring-summer reports of Emiliania huxleyi blooms around the North Sea and Norwegian fjords system we want to observe what happens in this side of the planet. To do that, we collected seawater containing planktonic organisms at the surface and in some stations up to 75 m depth. Inverted microscopy along with SEM analyses were used to identify and quantify the planktonic items.